An Investigation on Chinese Mobile Game Market Entry Strategy - Ying, Hong (2015)
This paper explores the Chinese market entry strategy for an independent mobile game company. The Chinese mobile games market has attracted worldwide attentions for its unprecedented growth. However, the industry is fairly complicated and incumbents have established some barriers for new entrants. The purpose of the paper is to discover the mobile game landscape in China and form tailored entry roadmaps for the client company. Relevant academic literatures was consolidated to form a theoretical framework on the methods of breaking into well-guarded markets. Investigations basing on the framework was conducted with primary and secondary data. The findings reveals that the industry and the market is unique. In order to profitably enter the Chinese market, the company needs to address two key problems: localised publishing strategy and localised product by utilising the combination of three approaches from the theoretical framework. The paper recommends an entry strategy of establishing partnership with suitable domestic publishers to launch the game.